PEMBERDAYAAN LEMBAGA KEUANGAN SYARIAH DALAM MENINGKATKAN PERAN INKLUSI KEUANGAN - Yolanda Masnita; Hermien Triyowati; Khomsiyah Khomsiyah (JUARA: Jurnal Wahana Abdimas Sejahtera, 2020)
With a large number of unbanked people in Indonesia, innovative access to Financial Inclusion is needed. Financial inclusion activities that aim to eliminate all forms of obstacles both in the way of prices and non-prices of public access to use or utilize financial services. Community Service - PKM, this time aims to increase the role of the financial services sector, especially to the owners, top management, and employees of several LKMS (Sharia Microfinance Institutions) - Sharia Rural Banks (BPRS), as executors or performers of financial activities inclusive which will have an impact on improving the welfare of the dhu'afa community, poverty alleviation and regional / regional economic development. This PKM is followed by the owner, top management, and employees of BPRS members as ASBISINDO - Indonesian Sharia Bank Association located in Greater Jakarta. The method used is to provide training through lectures, discussions, and questions and answers, then carried out focus group discussions and the distribution of questionnaires. The results show that the quality and speed of sharia banking services must continue to be improved, among others, by developing reliable and adaptive information technology. To accelerate the development of Islamic financial inclusion, it can be done by establishing a micro waqf bank or working together with Micro Sharia Financial Institutions (LKSM) such as Baitul Mal Wattamwil (BMT) or Islamic financial services cooperatives (KKJS), while maintaining prudential principles. BPRS is expected to continue to develop and monitor the implementation of Islamic financial inclusion through microfinance without collateral, qardhul hasan financing, or joint liability through group leaders or financing thaharah for low-income people.Keywords: Financial Inclusion, Unbanked - no bank account, LKMS - Islamic Microfinance Institution, Financial Services.